Legal analysis of land ownership disputes between bona fide purchasers and certificate holders: A case study of serang district court decision no. 121/pdt.g/2024/pn.srg - Abdul Muid; Asnawi Asnawi; Faturohman Faturohman (Journal of Law Science, 2024)
Land ownership disputes are common in Indonesia, especially when involving good faith buyers who have lawfully purchased and physically occupied land but do not yet possess an official land certificate. The discrepancy between physical control and formal ownership documents often leads to complex legal conflicts. In practice, the land law system tends to prioritize formal documentation over substantive justice, thereby disadvantaging honest parties who have acted in good faith. This study aims to analyze the legal protection for good faith buyers in land ownership disputes and to examine the legal considerations of judges in Decision No. 121/Pdt.G/2024/PN.Srg. The focus is on how the court evaluates the strength of formal certificates versus the legitimacy of transactions made by buyers acting in good faith. The research method used is normative juridical with a case study approach. Data was obtained through literature review, court documents, and relevant statutory regulations. The analysis was conducted qualitatively using legal certainty theory, legal protection theory, and substantive justice as analytical frameworks. The results indicate that the court prioritized the administrative strength of certificates as the primary basis in ruling the case. Although the defendant conducted a valid transaction and physically controlled the land, the court did not fully consider the element of good faith. This reflects the weak legal protection for good faith buyers and an imbalance between legal certainty and justice in the land dispute resolution process.